THE RELEVANCE OF THE IDEOLOGICAL VALUES OF SURA MAGADA IN CONTEMPORARY CONTEXT - Ida Bagus Wika Krishna; Ida Bagus Yudha Triguna; Ida Ayu Komang Arniati (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
This article attempts to describe the relevance of Sura magada's ideology in the Banjar War of 1868 with the present context. This study uses a qualitative approach. The research data was extracted through text studies, documents, in-depth interviews and field studies in Banjar village. The data in this study were collected using various techniques to obtain the required data with quality, reliability, and validity. The technique of determining information in this study uses purposive sampling technique. The data in this study were collected through observation, in-depth interviews, and document studies. The results showed that the ideological values of Sura magada in the Banjar War of 1868 were (1) the value of heroism, (2) the value of leadership, (3) the value of courage, (4) the value of self-sacrifice, (5) the value of authority, (7) values of patriotism, (8) moral values, (9) values of solidarity, and (10) religious values that are very relevant to be guided and become principles of life in various activities today. This research shows that the actions and behavior of Griya Gede Banjar and the Banjar people are inspired by the ideological values of Sura magada.